Branding and Strategic Positioning For Enhanced Performance among Online-Based Companies: An Empirical Study on Airbnb - Morris Karithi Njilu (SIASAT, 2023)
Airbnb has been known for extensive services in online home-sharing and promotion of travel and tour business. However, bearing to the increasingly changing environment and business trends across the globe, it is time for Airbnb to diversify and extend its services to other inter-related products. The proposed new product for Airbnb is development of online taxi service platform in the most toured areas and other upcoming markets. While Airbnb has recently relied on homeowners to rent out their cars to their clients, Airbnb can also go an extra mile and have its own taxi platform which can either be developed separately or integrated with the existing platform. Through the existing potential clients and homeowners at the Airbnb platform, the company will identify the most appropriate travel destinations to start the service. The company will market the service where local drivers can link up with the travellers and offer taxi services. With time, this service can be expanded to stand on its own brand and compete with other key players in the market like Uber. However, it is proposed that the service can be piloted by partnering with the existing online taxi service providers like Uber. The company will then start its own service after the reception of the piloted service. The main potential customers for this service will be the existing customers at Airbnb and other referrals as well as other customers from extensive marketing to be done on the service. The pricing strategy adopted for the service will be economy strategy where the costs of development and marketing will be minimized and the prices minimized as well so as to stand a chance to compete with the existing players.